Videoscene as a possibility of scenic time resignification and expansion - Andraus, Mariana Baruco Machado (Advances in Social Sciences Research Journal, 2018)
This work aims to discuss the notion of narrativity in dance from three pieces in which videoscenes were used as a resource for resignifying time perception in the scene. In each of them, the usage of video has a distinct function: in one of them, it represents memories of the main character; In another, it portrays the character’s pregnancy; In the third, it has two distinct functions: at times it functions as a flashback and, at other times, to represent the hallucination of the character in a feverish state. From these experiences, the developed proposal is that the projection of a videoscene over the live-action scene helped, in these pieces, the design of dramaturgic dance scripts that favored the fusion of scene with life, bringing the story closer to a "real" chronology – which is called, in this work, of “time resignifying the scene”, as an expansion of the scenic time.